Tolerance of sonidegib after intolerance of vismodegib-Experience in two patients with nevoid basal cell carcinoma syndrome (Gorlin syndrome) - Federico Venturi; Luciana Trane; Flavia Silvestri; Biancamaria Zuccaro; Elisabetta Magnaterra; Vincenzo De Giorgi (Wiley, 2023)
Abstract Nevoid basal cell carcinoma syndrome (NBCCS, Gorlin syndrome) is a rare genetic condition characterized by the early development of numerous cutaneous basal cell carcinomas (BCCs). Although most BCCs are surgically treated with total resection, some of the lesions may proceed to a locally advanced or metastatic stage. Systemic treatment with a hedgehog inhibitors (HHIs) such as Vismodegib or Sonidegib is indicated in this population. We report cases of two patients with confirmed diagnoses of NBCCS. Both patients had undergone multiple surgical excisions and had been treated with oral Vismodegib 150 mg/day for a locally advanced tumour. They both discontinued the therapy due to its specific adverse effects (AEs) and are now being treated with oral Sonidegib, which has had better tolerability and a complete response. The aims of this report was to demonstrate the efficacy of HHI treatment with Sonidegib in patients with NCBBS who had previously treated with Vismodegib but discontinued it because of its specific AEs. Our experience in two patients shows that Sonidegib can be considered in Gorlin patients intolerant but responding to Vismodegib.